Respuesta :

Answer:

C

Step-by-step explanation:

x = 2 in the interval x ≥ 2 , then g(x) = x³ - 9x² +  27x - 25 , so

g(2) = 2³ - 9(2)² + 27(2) - 25

      = 8 - 9(4) + 54 - 25

      = 8 - 36 + 29

      = - 28 + 29

      = 1

Answer:

C. 1

Step-by-step explanation:

  • [tex]g(x)=\begin{cases} \bigg(\frac{1}{2}\bigg)^{x-3}, {x<2} \\\\ x^3-9x^2+27x -25, {x \geq 2}\end{cases} [/tex]

  • g(2) lies in the interval[tex]x\geq 2[/tex]

  • [tex]\implies g(2) = (2)^3-9(2)^2+27(2) -25[/tex]

  • [tex]\implies g(2) =8-36+54 -25[/tex]

  • [tex]\implies g(2) =1[/tex]